Caracterização de metais no material particulado em suspensão em diferentes localidades no estado do Paraná - Miranda, João Paulo (2013)
The urban growth in several municipalities contribute in air quality deterioration due to emissions of gases and particles from various activities and processes, as well as by resuspension of particles previously fielded. The life quality, health and well-being of the population are directly influenced by the air quality since people are widely vulnerable to exposure of air pollutants through the breath. The present study evaluated the composition of metals in suspended particulate matter in urban environments with distinct influence activities. The sampling of Total Suspended Particulate (TSP) with High Volume Sampler was done in five locations of Paraná State that feature different characteristics of urbanization and industrialization. The results of concentration of TSP were compared to legal standards, which establish that the daily concentration must not exceed 240μg/m³, and the annual average must be less than 150 μg/m³. The concentration of TSP in 24 hours was greater than the limit in just one sampling (about 44% higher than the limit). However, when considering the mean concentration of seven consecutive days monitored at each site, two of the five sites had mean concentration higher than the primary air quality standard for the annual average. According to prior evaluation of the activities around the sampling areas were defined five targets metals (lead, calcium, chromium, iron and potassium). In general, the calcium was detected in higher concentrations for most of the samples, suggesting the soil as the main source of particulate matter. The samples composition, the local features identification and weather information were used to ascertain the main sources of particulate matter contribution and to suggest alternatives to improve the air quality.